2021
DOI: 10.3329/brc.v7i1.54253
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes of APEC (avian pathogenic Escherichia coli) isolated from poultry in Noakhali, Bangladesh

Abstract: Avian colibacillosis, caused by avian pathogenic Escherichia coli (APEC), is one of the major infectious diseases of poultry that bring about great economic loss for the Bangladesh poultry industry. The present study aimed to determine the virulence genes of avian pathogenic Escherichia coli (APEC) from cases of colibacillosis in poultry at the Noakhali district of Bangladesh. Currently, virulence-associated gene profiles of APEC isolates were investigated by polymerase chain reaction (PCR). A total of 24 (twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The present data-based study examines the global association between meteorological factors and Monkeypox cases. Various vector-borne zoonotic viral diseases including COVID-19, dengue, Chikungunia, malaria, Ebola, and Zika are increasing with changes in climatic conditions [ 31 , 32 , 33 , 34 , 35 ]. Previous studies have shown that meteorological factors affect the growth and activity of respiratory viral diseases including SARS-CoV [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present data-based study examines the global association between meteorological factors and Monkeypox cases. Various vector-borne zoonotic viral diseases including COVID-19, dengue, Chikungunia, malaria, Ebola, and Zika are increasing with changes in climatic conditions [ 31 , 32 , 33 , 34 , 35 ]. Previous studies have shown that meteorological factors affect the growth and activity of respiratory viral diseases including SARS-CoV [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to better understand how this virus spreads, additional research is needed about natural animal reservoirs and the evolving and changing epidemiology of the virus. 24,25,50 limitations Overall, 17 relevant articles were screened for comprehensive data extraction. However, there are also some limitations hardly could avoid.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] It remains as an important tool to express the fatality of the disease. [25][26][27] The CFR of MPXD can inform specific interferences and the public health scenario of this virus; the ratio of confirmed death patients and diagnosed positive patients number which is converted as a percentage. 8 The children are more vulnerable to MPXD and thus, the severity or fatality of MPXD is related to patient conditions and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Over 2 years, the SARS-CoV-2 virus has evolved through multiple new mutations and various genetic variants, such as Alpha (B.1.1.7) with seven, Beta (B.1.351) with nine, Gamma (P.1) with 12, Delta (B.1.6, B.1.6.2) with 17, Omicron (B.1.1.529) and Neocov variant with 32 new mutations in the spike protein gene ( Ahmed et al, 2021 ; Chakraborty et al, 2022a ; Chakraborty et al, 2022b ; Chakraborty et al, 2022c ; Chakraborty et al, 2022d ; Chakraborty et al, 2022e ). These variants have spread to various regions of the world, and among them, variants of concern (VOCs) such as Delta, Omicron, and their sub-lineages have caused significant risk to public health ( Hossain et al, 2021 ; Islam et al, 2021 , Islam et al, 2022a ). However, the number of fatalities caused by various SARS-CoV-2 variants fluctuates considerably ( Islam et al, 2022b ; Islam et al, 2022c ; Islam et al, 2022d ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the three significant mutations that the spike protein RBD carries, E484K is situated in a loop region away from direct hACE2 (human angiotensin-converting enzyme 2) contact, while mutations in P.1: N501Y and K417T interact with human ACE2 (hACE2). ( Faria et al, 2021 ; Hossain et al, 2021 ; Chandran et al, 2022 ). Compared with the first strain (alpha strain) of SARS-CoV-2, the Delta variant B.1.617.2 has 23 mutations.…”
Section: Introductionmentioning
confidence: 99%